Representasi Girl Power dan Perlawanan Domestifikasi Perempuan dalam Film Charlie’s Angel (2019 - Defa Ayu Triana; Prawinda Putri Anzari; Nanda Harda Pratama Meiji (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2021)
Various gender-biased films still place women as weak and only occupy tasks in the domestic sphere. There is still a public perception that women cannot carry out significant tasks in the public sector. This study aims to represent girl power and the resistance to female domestication through film media based on these problems. This study uses a qualitative method of John Fiske's semiotic analysis, including the code level of reality, representation, and ideology. The study results show that the power of women in the Charlie's Angel (2019) movie has intellectual abilities. They can become a leader, fighting negative stereotypes of society by maximizing the power of skills possessed, including self-defense, disguise, shooting, and a programmer who can hack security. The women in this film prove their resistance to women's domestication by working in the public sector, namely in an international-scale investigative security organization called the Townsend Agency.